2005
DOI: 10.1172/jci22365
|View full text |Cite
|
Sign up to set email alerts
|

The MODY1 gene HNF-4α regulates selected genes involved in insulin secretion

Abstract: Mutations in the gene encoding hepatocyte nuclear factor-4α (HNF-4α) result in maturity-onset diabetes of the young (MODY). To determine the contribution of HNF-4α to the maintenance of glucose homeostasis by the β cell in vivo, we derived a conditional knockout of HNF-4α using the Cre-loxP system. Surprisingly, deletion of HNF-4α in β cells resulted in hyperinsulinemia in fasted and fed mice but paradoxically also in impaired glucose tolerance. Islet perifusion and calcium-imaging studies showed abnormal resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(33 citation statements)
references
References 64 publications
1
29
0
3
Order By: Relevance
“…In contrast, numerous previous publications have shown that HNF4A gene mutations most often result in hyperinsulinemic hypoglycemia in the neonatal period [9], followed by a decline in β-cell function, leading to MODY1 at a later stage, suggesting a dual role of the transcription factor at different stages of life. The role of HNF4A in insulin secretion has been studied in transgenic mice in which HNF4A is deleted specifically in β-cells by crossing HNF4alpha loxP/loxP mice with mice expressing a Cre recombinase under the insulin promoter [16,17]. One study [16] showed that conditional deletion of HNF4A leads to lower blood glucose values associated with increased insulin levels in fasted and fed states in both neonates and 3- to 5-month-old mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, numerous previous publications have shown that HNF4A gene mutations most often result in hyperinsulinemic hypoglycemia in the neonatal period [9], followed by a decline in β-cell function, leading to MODY1 at a later stage, suggesting a dual role of the transcription factor at different stages of life. The role of HNF4A in insulin secretion has been studied in transgenic mice in which HNF4A is deleted specifically in β-cells by crossing HNF4alpha loxP/loxP mice with mice expressing a Cre recombinase under the insulin promoter [16,17]. One study [16] showed that conditional deletion of HNF4A leads to lower blood glucose values associated with increased insulin levels in fasted and fed states in both neonates and 3- to 5-month-old mice.…”
Section: Discussionmentioning
confidence: 99%
“…The role of HNF4A in insulin secretion has been studied in transgenic mice in which HNF4A is deleted specifically in β-cells by crossing HNF4alpha loxP/loxP mice with mice expressing a Cre recombinase under the insulin promoter [16,17]. One study [16] showed that conditional deletion of HNF4A leads to lower blood glucose values associated with increased insulin levels in fasted and fed states in both neonates and 3- to 5-month-old mice. Interestingly, this increased insulin secretion in a basal state was lost when the mice were challenged with intraperitoneal glucose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mouse models have shown that it is required in the pancreas for glucose-stimulated insulin secretion and beta cell expansion (Gupta et al 2005, 2007). HNF4α has pleiotropic roles in other enterohepatic tissues, most prominently in the liver, where it is required for the maturation, maintenance and differentiated functions of hepatocytes (Sladek et al 1990; Chen et al 1994b).…”
Section: Arrested Development: Orphans Of the Nr2a Groupmentioning
confidence: 99%